Manifestations of Social Cognition Through Collaborative Semantic Mapping in Mastering Complex Arabic Texts - Luluk Yulia Ma’wa; Latifatul Khoiriyah; Erlina (Al-Qalam: Jurnal Pendidikan Bahasa Arab, 2026)
Mastery of advanced Arabic texts with syntactic complexity (i‘rab) and rich morphological variation often triggers excessive cognitive load for second language learners. This study employs a descriptive qualitative approach to explore how social cognition phenomena manifest through the application of collaborative semantic mapping techniques. Grounded in Vygotsky’s sociocultural theory, data were collected through classroom observation, concept map document analysis, and in-depth interviews with learners. The descriptive results show that group interaction in constructing semantic maps converts external negotiation of meaning into directed internal individual processes. This technique transforms complex Arabic texts into macro and micro visual structures, triggers peer scaffolding, and significantly reduces obstacles to text comprehension. This article formulates the theoretical foundation, qualitative procedures, and pedagogical implications of sociocognitive interaction in advanced Arabic language learning.